Simultaneous allocation of DGs and remote controllable switches in distribution networks considering multilevel load model - Raoofat, M. (International journal of electrical power & energy systems, 2011)
► The paper proposes a new algorithm for sizing and siting of DGs. ► The objectives are loss reduction and reliability improvement. ► For a better reliability improvement, RCSs are also located simultaneously. ► A yearly multilevel load model is utilized for more accurate solution. ► A GA-based algorithm is used for optimization. Reliability improvement and loss reduction are two important goals in optimal sizing and siting of distributed generations (DGs). Also, remote controllable switches can be utilized in distribution networks to increase the role of DGs in reliability improvement. Therefore, this paper presents a GA-based method to allocate simultaneously DGs and remote controllable switches in electric distribution networks. The goal of proposed approach is reliability improvement and energy loss reduction. The optimal sizes of distributed generators are also determined during the optimization procedure. A multilevel yearly load model is utilized to achieve the optimal solution. Numerical studies on a 33-bus distribution network show satisfactory results.